(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Treatment of the syndrome of the dry eye in patients with scarring consequences of the eye burns is an urgent problem of ophthalmology. Purpose. To determine the level of the protective components of the tear fluid in patients with scarring consequences of the eye burns Material and Methods. Clinical investigations were made in patients with eye bums: 10 patients with severe consequences of bums who received complex treatment and 14patients with severe bums in whom complex treatment was complemented with preparations «Artifical tear» and «Restasis». The content of mucin, general protein and sulfhydric groups were determined in the patients’ tear fluid before and after treatment. The same investigations were made in 12 healthy persons. Results. It is established that patients with burns of the anterior section of the eye the thyol status of proteins and content of mucin are sharply disturbed while using the preparations «Artifical tear» and «Restasis», promotes the tendency to normalization of the level of general protein in the patients’ tear fluid. Conclusions. The application of the preparations «Artifical tear» and «Restasis» did not exert significant influence on the content of the thyol groups of mucin in the tear fluid, however, it resulted in marked decrease of the protein level in the tear in patients of the main group in comparison with the comparative group.